PENGUATAN PERLINDUNGAN HUKUM TERHADAP INVESTOR DALAM PENGEMBANGAN INVESTASI PADA BIDANG PARIWISATA DI KABUPATEN LOMBOK BARAT (KECAMATAN BATULAYAR) - Refnaldy Maulana; Eduardus Bayo Sili; Lalu Muhammad Hayyanul Haq (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
This study aims to find out to what extent or how to strengthen legal protection for investors in the development of investment in the tourism sector in West Lombok Regency by finding out how the legal protection framework is, the protective barrier factors and steps to strengthen the protection taken in order to achieve legal protection. By using normative legal research methods and empirical legal research methods that examine how exactly the exact steps can be taken to optimize legal protection for investors. The results of this study indicate that the problem of legal protection for illegal investors is very complex, which requires a legal protection framework starting from the harmonization of regulations from both the statutory level to the district/city regulation level. Then another thing that was obtained was the number of problems that arose which later became a factor that hindered legal protection for investors, both in terms of investors and other aspects that could cause obstacles to legal protection. Therefore, strengthening steps were taken to resolve problems and legal protection efforts.